(untitled) (Experimental biology, 2019)
An increase in the number of severe candidiasis, the growing incidence of antimicrobial resistance of the pathogens responsible for these infections, as well as their harmful side effects, necessitate developing new and more effective antifungal agents. In this context, the elaboration and utilization of functional fermented milk products with microorganisms harbouring antifungal activity and thus promoting the elimination of opportunistic Candida yeasts from the body, could be of great interest. The microbiota of Kazakh national sour-milk beverages derived from mare’s and camel’s milk has a multidirectional health effect on the human body, but the antagonistic activity of members of these microbiota against yeast species responsible for candidiasis have not yet been studied. The aim of this work was to isolate microorganisms, with antagonistic activity against Candida yeast species from Kazakh national fermented milk beverages. The study of antagonistic activities of various dairy products of local (both domestic and commercial) production against C. albicans using well-diffusion assays showed effective suppression of yeast growth with homemade koumiss samples. Associations of microorganisms from various koumiss samples also showed antagonistic activities after performing successive inoculations and fermentations of cow’s milk and whey. When cultured in cow’s milk, these associations had an increased activity against C. krusei 25. The highest antagonistic activity against C. glabrata 589 was found for three associations cultured in whey. After plating the most promising associations on MRS media, 41 bacteria with were isolated from selected associations based on their colony morphotype, 28 of which were lactic acid bacteria, while the other were presumptive acetic bacteria. Thirty-four yeast isolates were also selected. In the present study, autochthonous strains of microorganisms that inhibited Candida spp. growth, including Candida strains exhibiting a high resistance to both lactic acid bacteria metabolites (intestinal and vaginal isolates of C. albicans) and antifungal antibiotic fluconazole (C. glabrata 589 and S. krusei 25), were selected for the first time. The isolated microorganisms will be used to create consortia and apply as starters to develop new functional beverages with antifungal activity against opportunistic Candida yeast species. Key words/phrases: koumiss, lactic acid bacteria, Candida yeast antagonists.